A Global Solution On Taxing The Digital Economy: "Does Article 12B of the UN MC adequately solve the problems encountered by the adopted unilateral measures (DSTs) to taxing the Digital Economy?" - Mayebe, Francis (Department of Finance and Tax, 2024)
The rapid growth of the digital economy has created significant tax challenges, particularly for developing countries. As identified in this dissertation, the current tax framework is inadequate in solving the tax challenges as non-resident digital entities can generate income in a market/source jurisdiction without the need of having any physical presence. The OECD and the UN have been relentlessly searching for solutions to address the challenges of the digital economy. On the other hand, many states have not been patient enough to wait for a solution but have resorted to implementing unilateral measures in the form of Digital Services Taxes (DSTs) and equalisation levies. As it can be already noted from recent trends in international tax policy and seems, as well as the unilateral actions taken in the European Union (EU), that the permanent establishment nexus requirement to assume taxing rights is ill-suited to deal with certain complexities that can be ascertained from the core of the digital economy. It is clearly evident from the nature of the digital economy that an enterprise may attain a significant level of economic benefits in a foreign jurisdiction without having the physical factors embedded in the PE Principle. In this instance, it is widely seen that the digital enterprise or through the use of digital means, an enterprise without physical presence in the market jurisdiction may be entitled to a wide range of public benefits in that state which may include legal protection. In support of this argument, the EU has taken a view that a wide gap indeed exists between economic presence and physical presence in light of the increasing levels of technological advancement and increased globalization. It is certain from this view by the EU that one has seen an increase in unilateral measures to tax the digital economy amongst EU states through the introduction of the DST. The DST introduced in the EU states is targeted at taxing gross revenue in three instances: firstly, in instances where adverts are placed on the website, software or apps; secondly, where a digital platform allows users to find and interact with each other in a way that allows or facilitates the supply of goods and services; lastly, where data is collected by digital means and subsequently used to generate revenue. It is evident from the above that the measures adopted are narrowly focused on digital services that are reliant on user value creation. The United Nations made a shift away from an intense physical presence requirement by first introducing Article 12A into its Model Tax Treaty which allowed states to tax fees paid for technical services irrespective of physical presence in the source country. In a recent case, the US Supreme Court made an interesting finding in South Dakota v Wayfair, were it held that all states have a right to impose taxes on supplies made to their residents by non-residents irrespective of the lack of physical presence by the supplier in that instance. It is in this light clear that the introduction of Article 12B by the United Nations is a drive towards the right direction in solving the issue of taxing the digital economy. Article 12B which is focused on taxing Automated Digital Services (ADS) seeks to provide a way in which market jurisdictions can benefit from taxing entities participating in their markets without much physical presence. It gives an opportunity to avoid double taxation resulting from unilateral measures discussed above and by using a system of withholding taxes, it could potentially increase compliance and reduce disputes around interpretation. However, Article 12B also poses a few concerns in its application such as containing a ring-fencing proposal, the uncertainty of the concept of payer and the use of the gross income as a fundamental basis for calculations. It is certainly clear that it has weaknesses and strengths, and it is upon this basis that l will be exploring its application further in the relevant chapters.